La aplicación de estrategias lúdicas para el desarrollo del lenguaje oral en niños y niñas del nivel II del centro municipal de educación inicial de “Cotocollao”, de la ciudad de Quito, período lectivo 2014-2015 - Cazar Romero, Sandra Piedad (2015)
This research workis titled"" THE APPLICATION OFLEISUREFORORALLANGUAGEDEVELOPMENTINCHILDRENOFMUNICIPALLEVELIIEDUCATIONCENTERINITIALSTRATEGY"Cotocollao" QUITOCITY, ACADEMICSESSION2014-2015".se hasstructured and developedaccordingto the Regulations ofGraduationNational University ofLoja.The researchfocusesongeneral objective: Emphasizeplayful strategiesas the focus ofdevelopment in theorallanguage ofchildren. The methods used were: Scientist, Inductive-Deductive, Descriptive andStatisticalModel, techniques and toolswe use are:SurveyAppliedtotheTeachersto establishthe use ofplayful strategiesinchildrenat LevelIIof theMunicipalCenter forEarly Educationof"Cotocollao" CityofQuito,2014-2015school year, Observation Guideapplied tochildren's initial levelIIin order toassess the level ofdevelopment oflanguage presentedin the students. Of theteachers surveyed, 100% reported learning about thefun, just as 100% responded Usingplayful strategiesaffects the developmentof oral language.After applyingObservation Guidetochildrenof the InitialLevelII, concerningthe level oflanguage development,the most significantresults showedthat 77.4% alonecan namebody parts, exceeding 50 %childrenpronounce thephonemesch,l, ñ, r, s, ll, rr; childrenshowed42.5%usingsocially constructedforms ofexpression. These resultsallow us toconclude that: Applying playful strategiesaffect theoral language developmentofchildren fromtheMunicipalLevelIIEarly EducationCenter"Cotocollao" CityofQuito,2014-2015school year